Hands-on + : - Metzelaar, Lawrence (Benjamin/Cummings Pub. Co., 1991)
This handy Pocket Reference will be your constant companion. It fits in your shirt pocket and it is always available to you, when you need it. Size ( 3.5 x 6.5 inches) - just perfect. Here You will find everything you need to know about MS-DOS. Covers all versions from 3.3 up to the latest version 6.2 Concise explanations of all DOS commands illustrated with an easy to follow example.